Identity The Identity of the Bissu Soul in the Perspective of Sufism: Identitas Jiwa Bissu Dalam Perspektif Tasawuf - Muh Fariz Abdul Khalil; Muhammad , Firdaus; Awal Muqsith (Jurnal Diskursus Islam, 2026)
This study aims to analyze the nature of the Bugis Bissu’s spiritual identity and to understand the Islamic Sufi perspective on that identity. This is a field study employing a qualitative-descriptive approach that incorporates Sufi and philosophical perspectives. Primary data were obtained through interviews with Bugis Bissu, while secondary data were derived from literature, including books, journals, and academic articles. Data analysis was conducted through a process of data reduction and presentation. The results of the study indicate that the spiritual identity of the Bugis Bissu is a spiritual-cultural identity shaped by Bugis cosmology, which emphasizes the unity of masculine and feminine elements within the human being. This identity is not understood merely as a biological identity but rather as a sacred spiritual role recognized within the social-religious order of Bugis society. From an Islamic Sufi perspective, the Bissu’s spiritual identity is understood as a form of spiritual quest oriented toward devotion and inner purity, though it has not yet attained the level of a perfected soul (nafs al-muṭma’innah). Bissu spiritual practices remain tied to local symbols and cosmology; thus, they are more appropriately situated at the intermediate levels of the soul, such as the nafs al-lawwāmah or the nafs al-mulhimah, which indicate a spiritual orientation but have not yet attained complete inner peace according to the teachings of Islamic Sufism.